2015
DOI: 10.1080/23279095.2014.978451
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Language Tests in Dementia Diagnosis in English-Speaking Hispanic and Non-Hispanic White Outpatients

Abstract: Neuropsychological language tests have limitations (e.g., unrepresentative norms) when applied to “Hispanics” of which clinicians are likely aware that may lead to inaccurate dementia diagnoses. Therefore, it was hypothesized that language tests would be weaker diagnostic predictors in Hispanics versus “non-Hispanic Whites.” Participants included 436 English-speaking Hispanic and 436 non-Hispanic White (randomly selected from 10,937) outpatients classified as dementia or normal cognition at initial evaluation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…One study investigated the Boston Naming Test and did not find significant differences in performance by H/Ls compared with non‐H/L groups (Supplementary File 2, Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study investigated the Boston Naming Test and did not find significant differences in performance by H/Ls compared with non‐H/L groups (Supplementary File 2, Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…One study investigated the verbal fluency test using the sample of the ADRC and found no significant difference in performance (animals and vegetables) between H/Ls and non‐H/Ls . The study with random population sampling in New Mexico, however, found significant differences in test performance (same‐sex first names) for H/L ethnicity (Supplementary File 2, Table S2).…”
Section: Resultsmentioning
confidence: 99%